On the Lie algebra structures connected with Hamiltonian dynamical systems - Smirnov, R.G. (Український математичний журнал, 1997)
We construct the hierarchies of master symmetries constituting Virasoro-type algebras for the Hamiltonian vector fields preserving a recursion operator. Similarly, repeatedly contracting a Hamiltonian vector field with the corresponding recursion operator, we define an Abelian Lie algebra of the thus obtained hierarchy of vector fields. The approach is shown to be applicable for the Volterra and Toda lattices. Для гамільтоиових систем з рекурсивним оператором ієрархії будується мастер симетрій, які формують алгебри Лі типу Вірасоро. Аналогічно, повторно діючи рекурсивним оператором на гамільтонів потік, одержується ієрархія векторних полів, що складають абелеву алгберу Лі. Цей підхід застосовано до систем Вольтерра і Тода.